Novel Nanoparticle Biomaterial of Alginate/Chitosan Loading Simultaneously Lovastatin and Ginsenoside RB1: Characteristics, Morphology, and Drug Release Study - Quan Vo-An; Thuy Chinh Nguyen; Quang Tung Nguyen; Quoc Trung Vu; Cong Doanh Truong; Thi Len Nguyen; Thi Ngoc Lien Ly; Long Giang Bach; Hoang Thai (International Journal of Polymer Science)
Recently, plenty of interesting studies on improvement of bioavailability for poorly soluble drugs were implemented with different approaches such as using of combined biopolymers as a delivery system that allowed to enhancing drug solubility and bioavailability. In this work, alginate and chitosan were blended together in the form of polymeric particles, loaded with both lovastatin and ginsenoside Rb1 to producing the four-component nanoparticles by ionic gelation method. CaCl2 and sodium tripolyphosphate were used as gelation agent and cross-linking agent, respectively. The characteristics of obtained nanoparticles were studied by means of infrared spectra (IR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and dynamic light scattering (DLS). In combination, ginsenoside Rb1 and lovastatin both interacted with each other to improve the drug release ability of the polymer particles. The change of initial content of drugs in the nanoparticles has a negligible effect on the functional groups in the structure of the nanoparticles but has a significant impact on drug release process of both lovastatin and ginsenoside Rb1 from the nanoparticles in selective simulated body fluids. In addition, the synergistic interaction of lovastatin and ginsenoside Rb1 could be also observed through the modification of relative crystal degree and drug release efficiency.